Digital Story Conceptual Change Oriented (DSCC) to Reduce Students’ Misconceptions in Physics - Kurniawan, Yudi; Muliyani, Riski; Nassim, Shahala (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2019)
The development of digital story conceptual change-oriented (DSCC) has been implemented to reduce the number of students' misconceptions. In this study, DSCC is reviewed based on the story aspect. This experimental design study used a one-group pretest-posttest design. The sampling in this study was taken by a purposive technique involving 114 students from two districts. The diagnostic instrument used was four tier-test and rubrics for assessing the story aspect of DSCC. In determining the decrease of the students' misconceptions, the researchers use the DQM formula. The analysis of DSCC’s assessment result was done using a holistic method. The result of the study shows that there was a decrease in the number of students' misconceptions within the high category. The highest number of the student who decreases after the implementation of DSCC was 100% and that statement of misconception was: "every motionless object has no energy". On the other side, the result of the story aspect assessment shows that there was 20% of students gave negative comments for DSCC’s sequence/chronology events and 10% of the state that the location/ plotting of places was inappropriate(out of character). It is recommended for further research to consider the learning model to optimize the minimalization of the number of students' misconceptions.